Food plant extracts for sleep-related skin health: Mechanisms and prospects. (October 2022) - He, Bingwei; Chen, Yueyue; Yu, Shishuai; Hao, Yining; Wang, Feifei; Qu, Liping
Abstract: Chronic sleep deficiency, a public health epidemic, triggers an elevated risk for physical and mental disorders and may cause unpleasant sensations or experiences in daily life. Importantly, sleep-associated skin diseases attract public attention because most people have anxiety about their facial appearance in modern society. Amounts of health food, especially derived from edible and efficient plant extracts, have been developed for skincare via improvement of sleep quality. Mechanisms of good sleep and healthy skin have been studied, however, the relationship between sleep-promoting herbs and skincare is less elucidated. In this review, we summarize the main signaling pathways of neurotransmitter-mediated skin beauty and list dozens of functional plant extracts for sleep assistance. We conclude several plant candidates for oral cosmetics application through sleep-related neurotransmitters regulation. This review provides pieces of evidence for the application of oral cosmetic food derived from plant extracts in sleep-related beauty.